Optical super-high magnification dermoscopy of benign and malignant melanocytic lesions in correlation with histopathology - Winkler, Julia K.; Kommoss, Katharina; Vollmer, Anastasia S.; Enk, Alexander; Hänßle, Holger; Toberer, Ferdinand (Journal der Deutschen Dermatologischen Gesellschaft, 2025)
Background and objectives Technical advances have allowed for significant improvements in imaging techniques in recent years. Specifically, lesions can now be depicted at a much higher magnification - up to 400 x - using optical super-high magnification dermoscopy (OSHMD). Patients and methods This is a retrospective, observational study assessing 99 melanocytic lesions in patients from the University Hospital Heidelberg. Dermoscopy (20 x) and OSHMD images (90 x, 120 x, 150 x, 180 x and 270 x) were acquired. OSHMD images were assessed for the presence/absence of pigment network, distribution, size and color of cells, dots and roundish nests (small/large), structureless areas and vessels in nevi versus melanomas. Correlation studies with histopathology were performed. Results We found that in OSHMD atypical pigment network, irregular dark dots, atypical vessels and irregular grey out-of-focus cells are clues to melanoma. Black dots and small roundish nests in OSHMD images corresponded to nests of atypical melanocytes in melanomas in histopathology. Grey out-of-focus cells in OSHMD images corresponded to melanophages in histopathology and in irregular distribution were found more frequently in melanomas. Conclusions We conclude that knowing about histopathological correlates OSHMD may support differentiating nevi from melanomas.
Gesehen am 21.07.2025
Online veröffentlicht: 28 February 2025